Usages littéraires du merveilleux et effets d’attestation dans les littératures subsahariennes (Kwahulé, Mukasonga, Tchak) - Coste, Marion (Revue critique de fixxion française contemporaine, 2022)
This article focuses on Les Fables du moineau by Sami Tchak, Monsieur Ki by Koffi Kwahulé and Cœur Tambour by Scholastique Mukasonga. It is a question of analyzing the types of authority summoned in these stories. A first authority, moral, is based on a documentary value, the story translating sociological realities or belief systems attributed to sub-Saharan cultures, particularly through the use of the marvelous genre or the recall of the codes of the traditional tale, in the work of Sami Tchak. However, this authority, which would tend to undermine the artistic significance of the work, is counterbalanced by another type of authority, properly literary. The latter is expressed first of all by the emphasis on numerous stylistic effects, particularly in moments that call for the marvelous, which show the singularity of the writing of each author. It is also expressed through the effects of irony and by creating a distance, through the insertion of Western narrators (Mukasonga) or the figure of a doubtful reader (Kwahulé), which introduces into the stories a plurality of points of view and a critical distance on certain magico-religious explanations which are presented, at another level, as the expression of sub-Saharan cultures. Cet article porte sur Les Fables du moineau de Sami Tchak, Monsieur Ki de Koffi Kwahulé et Cœur Tambour de Scholastique Mukasonga. Il s’agit d’analyser les types d’autorité convoqués dans ces récits. Une première autorité, morale, s’appuie sur une valeur documentaire, le récit traduisant des réalités sociologiques ou des systèmes de croyances attribuées à des cultures subsahariennes, notamment à travers l’usage du registre merveilleux ou le rappel des codes du conte traditionnel, dans l’œuvre de Sami Tchak. Cependant, cette autorité, qui aurait tendance à minorer la portée artistique de l’œuvre, est contrebalancée par un autre type d’autorité, proprement littéraire. Cette dernière s’exprime tout d’abord par la mise en exergue de nombreux effets de style, tout particulièrement dans les ...